Tumor-Stroma Ratio Is an Independent Prognostic Factor for Distant Metastasis in Squamous Cell Lung Cancer Following Resection - Fuman Wang; Yue Zhang; Dawei Li; Yifan Chi (Canadian Respiratory Journal)
Cancer distant metastasis is one of the main causes of cancer progression and difficulty in treatment (Rossi et al., 2020). This abstract aims to summarize the significance of tumor-stroma ratio (TSR) as a prognostic factor in the development of distant metastasis in squamous cell lung cancer (SQCLC) patients. The TSR has recently been recognized as a novel and independent prognostic parameter for a variety of solid tumor types (Lu et al., 2023). A total of 86 patients with SQCLC who had undergone surgery were included in the present study. Two independent observers visually identified TSR on hematoxylin and eosin (H&E)–stained pathological histologic sections. Patients were separated into two groups: stroma-rich, with a ratio of stroma as > 50%, and stroma-poor, with a ratio of stroma as ≤ 50%, which included a total of 36 and 50 patients, respectively. In the current study, the overall survival and no distant metastasis survival of patients in the stroma-poor group were improved compared with the stroma-rich group, and the overall risk of patients in the stroma-poor group was reduced compared with the stroma-rich group (p<0.05). In the multivariable analyses, the TSR was recognized as an important prognostic indicator for overall survival (HR = 2.41; p<0.001) and no distant metastasis survival (HR = 2.27; p<0.001). The study revealed that in patients with SQCLC, stroma-rich tumors were associated with a shorter distant metastasis-free interval and poorer prognosis compared to stroma-poor tumors. These findings suggest that the TSR may serve as a novel prognostic indicator for predicting distant metastasis in SQCLC.